Implementasi Perjanjian Jual Beli Padi Dengan Sistem Ijon: (Studi Kasus Desa Darek Kecamatan Praya Barat Daya Kabupaten Lombok Tengah) - Latifa, Nurul; Andriyani, Shinta (Private Law, 2022)
This research has the purpose to find out clearly how the implementation of the rice purchase agreement with Ijon System in Darek Village, West Praya district, Center Lombok Regency and How the ijon buy and sell systems based on the Indonesian Civil Code and Islamic law. This research has been doing by implemented the normative-empirical legal research method that using a statute approach, a conceptual approach, and a sociological approach. Based on the research problem and the purpose of the study namely the deep analysis of how the implementation of the ijon buy and sell rice system from the beginning of implementation until the end of the ijon buy and sell rice system. Because of this, the researcher found out the validity of the Ijon buy and sell rice system based on Indonesia Civil Code and Islamic Law